Metagenomic Next-Generation Sequencing of Cerebrospinal Fluid for the Diagnosis of Cerebral Aspergillosis - Xing, Xiao-Wei; Yu, Su-Fei; Zhang, Jia-Tang; Tan, Rui-Shu; Ma, Yu-Bao; Tian, Xia; Wang, Rong-Fei; Yao, Guo-En; Cui, Fang; Gui, Qiu-Ping; Yu, Sheng-Yuan (Frontiers in Microbiology, 2021)
Purpose: Cerebral aspergillosis (CA) is a rare but often fatal opportunistic infection that remains difficult to diagnose. The application of metagenomic next-generation sequencing (mNGS) in the diagnosis of CA remains poorly characterized. Here, we evaluated the usefulness of mNGS performed on CSF for the diagnosis of CA. Methods: This prospective study involved seven consecutive patients with confirmed CA in whom CSF mNGS was performed. A comparison of serum (1→3)-β-D-glucan, serum galactomannan, histopathological examination and mNGS of CSF were conducted. Results: mNGS of CSF was positive in six of the seven confirmed CA, i.e. 85.7% sensitivity. In the CM group, which was used as control group, mNGS of CSF was positive for Aspergillus in two patients, i.e. 84.6%specificity. Among the six mNGS positive cases, more than two Aspergillus species were found in four (4/6, 66.67%) cases. Conclusions: mNGS is helpful for the diagnosis of CA and may reduce the need for cerebral biopsy in patients with suspected CA.